Uncertain consumption practices in an uncertain future - VITOR M. LIMA; LUÍS A. PESSÔA; RUSSELL W. BELK (Cadernos EBAPE.BR, 2022)
Abstract This special issue of Cadernos EBAPE.BR sought to provoke a reflection focused on uncertain consumption practices in an uncertain future. While prior marketing and consumer research has explored consumer practices framed by an institutionalized, known, and more or less predictable context, the set of articles approved in this edition reveals different nuances. From experiential accounts of grief to the role of music in coping with the struggles of isolation to the overlap of social roles, these papers may help us to reflect on what we can do together, as a society, to tackle the challenges brought by COVID-19 not only at the local level but also globally.